Perlindungan Hukum Terhadap Kerugian Konsumen Atas Wanprestasi Pelaku Usaha Jasa Titip Beli Barang Secara Online - Pratiwi, Tiara; Syuhada Lubis, Mhd. Teguh (LPPM Universitas Ekasakti Padang, 2024)
This research is aimed at finding out the legal protection given to consumers for the performance of the entrepreneur of services to buy goods online contained in article 4 of the Act No. 8 Year 1999 where there are many cases of fraud such as uncertainty of the quality of the goods purchased because of the fact that they cannot see them in person. Sometimes goods purchased are not as expected and there is a risk of fraud, where the goods already purchased did not arrive or differ from the one ordered. Not all online sellers are reliable, and often there are cases of frauds in which consumers have transferred money but the ordered goods do not arrive. The type of research used is normative legal research, which is obtained from library materials or secondary data.